Effects of Freeze-Thaw Cycles on the Flavor of Nanguo Pear - Ge Bai; Ya Wang; Jianrong Zheng; Xiaomin Zhang; Zhaoyue Zhuang; Danshi Zhu; Xuehui Cao (Polish Journal of Food and Nutrition Sciences)
Frozen pears, obtained by repeated freezing and thawing under cold outdoor conditions in winter, are very popular in northeast China. The effects of three freeze-thaw cycles (FT1–FT3) on Nanguo pear flavor were studied under fast (−80°C) and slow (−20°C) freezing conditions. Significant differences were found in the flavor of Nanguo pear after subsequent freeze-thaw cycles. The total soluble solid (TSS) content of fresh pear was 14.17 g/100 g and increased significantly after the first freeze-thaw cycle to 17.57–18.17 g/100 g. Lower TSS content was found in pears after the repeated freeze-thawing process. Citric acid was determined as the main organic acid of Nanguo pear. Its content and the overall content of organic acids decreased successively after each freezing and thawing cycle. The electronic tongue analysis results showed that the sourness of fresh pears generally decreased after their repeated freezing and thawing, that the odor of Nanguo pear changed significantly after freeze-thaw cycles, and that nitrogen oxides and hydrocarbons were the most differentiating odor compounds. The content of ethyl caproate was the highest in the volatile compound profile of the Nanguo pear and ranged from 377.26 to 526.77 μg/kg. In short, after repeated freezing and thawing, the changes in the chemical composition impart the frozen pear a unique flavor.